2003
DOI: 10.1139/z03-181
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosis patterns in the postcranial skeleton and hyoid bones of the harbour porpoise (Phocoena phocoena) in the Baltic and North Sea

Abstract: The onset and timing of epiphyseal ankylosis in the vertebral column and flippers and ankylosis of the hyoid and sternal bones were studied in 350 skeletons of the harbour porpoise (Phocoena phocoena) originating from the Baltic and North Sea and held in the collections of the Zoological Museum (University of Copenhagen), the Museum of Natural History (Gothenburg), the National Museum of Natural History (Stockholm), and the German Oceanographic Museum (Stralsund). Epiphyseal ankylosis in the vertebral column s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 11 publications
3
55
0
Order By: Relevance
“…During the Pattern 2, we noticed unclear differences between the sexes, however, the females UFSC 1281 and 1285 showed a more advanced stage of ontogenetic development than the two males UFSC 1126 and 1368 of almost the same age. Some authors suggest that in the second phase (Pattern 2) the trend of the Pattern 1 reverses itself and females subsequently begin to grow faster (Read et al, 1993;Galatius and Kinze, 2003). According to Read et al (1993), male and female Tursiops truncatus from Sarasota (U.S.A.) showed distinct patterns of growth and achieved different final body lengths.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the Pattern 2, we noticed unclear differences between the sexes, however, the females UFSC 1281 and 1285 showed a more advanced stage of ontogenetic development than the two males UFSC 1126 and 1368 of almost the same age. Some authors suggest that in the second phase (Pattern 2) the trend of the Pattern 1 reverses itself and females subsequently begin to grow faster (Read et al, 1993;Galatius and Kinze, 2003). According to Read et al (1993), male and female Tursiops truncatus from Sarasota (U.S.A.) showed distinct patterns of growth and achieved different final body lengths.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were separated into patterns of column fusion based on the degree of fusion of the epiphyses to the vertebral body, as well as analysis of the G.L.G. The degree of epiphyseal fusion of the vertebral column was based on Galatius and Kinze (2003) (Figure 1): (A): no fusion -both epiphyseal plates free or not yet ossified; (B): initial fusion -at least one epiphyseal plate loosely fused to the centra; (C): progressing fusion -both epiphyseal plates fused to the centra, displaying clear sutures; (D): complete fusion -both epiphyseal plates fused to the centra, displaying no sutures. Specimens in the initial growth phase, i.e., with the entire vertebral column in degree A of epiphyseal fusion or with the beginning of epiphyseal fusion only on the cervical vertebrae, were considered calves in the broad sense (Pattern 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Danish population of porpoises all cervical vertebrae are fused in age group 6-7 years (females) and age group 10-13 years (males) (Galatius and Kinze 2003). A subadult, not yet sexually matured individual, was documented with a 63 mm long pelvic bone.…”
Section: Whalesmentioning
confidence: 98%
“…The fusion pattern of a large sample of Danish harbour porpoises showed that fusion starts in the cervical region and proceeds from both ends terminating in the thoracic region, and physical maturity, i.e. complete fusion of all vertebrae is achieved very late in an individuals life (Galatius and Kinze 2003).…”
Section: Whalesmentioning
confidence: 99%